Analysis of self-perceived use of spectrum of teaching styles in Italian physical education teachers - Monacis, Domenico; Latino, Francesca; d’Arando, Cristina; Bibba, Matteo; Annoscia, Sabrina; Pascali, Giacomo; Sannicandro, Italo; Colella, Dario (Frontiers in Sports and Active Living, 2024)
Introduction The present study aims to assess PE teachers' perception about the use of teaching styles during curricular lessons. Methods The sample involved a total of 83 PE teachers (M = 41, F = 42, main age = 43,74 ± 10,76) divided according to years of service (0–4 = 36%, 5–10 = 34%, and over 10 = 30%) and academic training (Higher Institutes of Physical Education = 44% and master's degree = 56%). Teachers complete a digitalized version of a self-produced questionnaire to assess how many times they use each teaching styles during the last month. Results Results show that (a) reproduction rather than production teaching styles were often used, while reproduction teachings styles were most frequently used regardless of years of service. Discussion Future research should investigate PE teacher's behavior to enhance the quality of physical education in school.